Financial contagion : the viral threat to the wealth of nations - Kolb, Robert W. , 1949- (Hoboken, New Jersey : Wiley, 2011)
"The latest insights on financial contagion and how both nations and investors can effectively deal with it The domino-style structure in which the financial system exists is a perilous one. Although historically, the financial system has been able to deal with major shocks, the fact remains that our financial system is not as secure as it should be. Recent years have brought about too many examples of contagion and systemic risk. That is why Financial Contagion is such an important read. In it, the serious concerns that revolve around our fragile economic system are investigated, researched, and explained. Throughout the book, Kolb offers valuable insights on this dilemma as he compiles the history of financial contagion, highlights the latest research on systemic failure and interrelated markets, and analyzes the risks and consequences we face moving forward. Examines the importance of careful regulation and what must be done to stabilize the global financial system Includes contributed chapters from both academics and experienced professionals, offering a variety of perspectives and a rich interplay of ideas Details how close we are to witnessing a financial contagion that could devastate the world economy We have been harshly reminded of how fragile our economic ecosystem is. With Financial Contagion, you?ll hold a better understanding of what needs to be done to strengthen our system and safeguard our financial future." Provided by publisher
1. Contagion: theory and identification -- 2. Contagion and the Asian financial crisis -- 3. Contagion and emerging markets -- 4. contagion in the financial crisis of 2007-2009 -- 5. Regional contagion -- 6. Contagion within an economy
Includes bibliographical references and index
Keywords: Financial crises; Financial risk management; International finance